Development of a Cereal Bar Product from Broken Organic Brown Rice: Development of a Cereal Bar Product from Broken Organic Brown Rice - จิตตะปาโล ผู้ช่วยศาสตราจารย์ ดร.ทุติยาภรณ์; วิทยาภรณ์ ดร.วราภรณ์; วิทยาภรณ์ ดร.วราภรณ์; วิรุฬห์ธนกฤษณ์ วีระพงศ์ (Journal of Food Health and Bioenvironmental Science, 2017)
This research aimed to survey consumer’s attitudes toward cereal bars, to develop a product using a commercial product as a prototype, and to analyze physical, chemical, and microbiological qualities and consumer acceptability of the developed product. In addition, the cost analysis and value addition of the broken organic brown riceenriched cereal bar found that 78.5% of consumers were interested in the developed cereal bar made from broken organic brown rice. The developed product consisted of 66% crispy rice from broken organic brown rice, 15% honey, 9% pop rice, 4% glucose syrup, 2% white sesame, 2% black sesame and 2% perilla. The chemical composition of the cereal bar composed of 69.66% carbohydrate, 19.17% fat, 6.18% protein, 4.24% moisture and 0.75%, ash and it provided 475.89 kcal / 100 g. Microbiological quality showed that this product was safe to consume. The acceptability test found that 73.3% of consumers were interested in this cereal bar, with a score of overall liking, using 9-point hedonic scale, equal to 6.7. The cost of each cereal bar made from crispy rice from broken organic brown rice, pop rice, honey, white and black sesame and perilla as organic ingredients was 10 Baht/bar; in contrast, using crispy rice and pop rice as the only organic ingredients would instead cost 6 Baht/bar.